Website-Based Sales Reporting Information System with the Laravel Framework (Case Study of Pramana Agency) - Prapbowo Ignatha Dharma; Sumarno Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
The rapid development of technology has a big role in facilitating all human activities. Technology was created to speed up work and make it more efficient. One form of existing technology is information systems. The operating system is a system that exists within an organization, intending to meet data processing needs, supporting operations, managerial and strategic in an organization and agency by providing reports to certain parties. One of the companies engaged in trading, namely Praman Agency, is in dire need of information system technology that provides sales data recap functions and sales profit reports. Activities in the company are currently still recorded manually in an Excel file, even though sales are made through marketplaces such as Shopee and Lazada. By looking at the picture of the workflow, in reality, the idea arose to create a Website-Based Sales Reporting Information System with the Laravel Framework (Case Study of Pramana Agency). An information system is needed by this company as well as other companies that run a similar business model, to facilitate sales reporting so that their business can be measured. This system also makes it easier for business owners to view daily sales reports so they can determine marketing strategies for the future.